Effects of Class II elastics on lower incisors during treatment with clear aligners vs. fixed appliance: a randomized clinical trial - Laganà, Giuseppina; Malara, Arianna; Lione, Roberta; Bollero, Patrizio; Cozza, Paola (Frontiers in Dental Medicine, 2025)
AimTo analyze the inclination of the lower incisor in patients with Class II malocclusion treated with elastics and clear aligners compared to a group wearing the same elastics and fixed appliance.Trial designProspective two-arms parallel group randomized clinical trial with a 1:1 allocation ratio.Materials and methodsA sample of 40 patients (19M and 21F), mean age 15.4 ± 1.8 years, was collected from the Department of Orthodontics at Policlinico Tor Vergata (Rome), and was randomly divided in two groups: Invisalign clear aligner group (AG), which consisted of 20 subjects (8M, 12F) and multibracket fixed appliance group (MBG), composed by 20 patients (9M, 11F). The subjects were selected according to inclusion criteria: full permanent dentition (excluding third molars), Class II molar relationship (2.5–4 mm), no history of orthodontic treatment. For each participant of the study, dental and aesthetic measurements, both millimeter and angular were performed on the lateral cephalogram at time T0 (before treatment) and time T1 (after 18 months of treatment).ResultsIn the short term (T1-T0 = 18 months), the analysis of the results showed no statistically significant changes in all evaluated parameters (IMPA, L1/A-Pg, Md1-TVL, LLA-TVL, p > 0.05). Therefore, there were no statistically significant change in the inclination of the lower incisors.ConclusionsThe use of Class II elastics in AG group showed a better control of the lower incisors' inclination, compared to the MBG group. Therefore, aligners represent a good alternative in the correction of mild Class II malocclusion in cases where the lower incisors proclination is undesirable.Trial RegistrationClinicalTrials.gov (registration number: NCT06832475).